Influence of facial threading on various physiological parameters of the skin: non-randomized trial involving adult women in Taiwan - Li-Ying Lin; Shang-Chia Chiou (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Background: Facial threading involves the removal of hairs to restore facial skin smoothness. However, its effectiveness has not been rigorously evaluated. Objective: To evaluate effects of facial threading on skin roughness, hydration, melanin index, and vellus hair on the face, complemented by a subjective evaluation of the tactile feel of the skin and improvement in skin color. Method: Participants who had not used exfoliators for two weeks before the experiment were included. Each participant underwent one session of facial threading every 21 days, for a total of 3 sessions. A three-dimensional skin roughness instrument and a multifunctional skin testing system were used to evaluate changes in roughness, hydration, and pigmentation on the forehead, cheeks, and corners of the mouth. A photomicrographic camera was used to record changes in vellus hair. Subjective reports of skin smoothness and color were recorded. Result: Eighteen participants completed the study. Facial threading produced a significant decrease in skin roughness on the forehead (22.42%, p = .013), right cheek (77%, p = .02), and left corner of the mouth (33.02%, p = .001). Subjective improvement in tactile feel of the skin and coloring were reported. Study Limitations: The study did not include randomization, with further limitations of a small sample size and a single site. Conclusion: Facial threading reduced skin roughness by 26.74% after three threading sessions, with improved subjective assessment of tactile feel and coloring. Future research should include a comparison with other cosmetic products with similar beautifying effects or a control group.